Prevalence and Risk Factors of Perinatal Asphyxia in a Tertiary Care Level Hospital, Harari Regional State, Ethiopia - Jamie, Arif Hussen; Abdosh, Mohammed Z (Journal of Nepal Paediatric Society, 2019)
Introduction: Globally birth asphyxia continues to present a major clinical problem. It is one of the common and leading causes of perinatal and neonatal mortality and morbidity especially in developing countries. Methods: A cross-sectional study was conducted among newborns in a tertiary level hospital, Ethiopia from February to July 2019. Systematic random sampling technique was used to select the study subjects. Multivariate logistic regression analysis was used to identify factors associated with the perinatal asphyxia among newborns. Results: Of the newborns, 32% had perinatal asphyxia and factors significantly associated were anaemia during pregnancy (adjusted OR = 2.99, 95% CI: 1.07 – 8.35), chronic hypertension (adjusted OR = 4.89, 95% CI: 1.16 – 20.72) and low birth weight newborns (adjusted OR = 3.31, 95% CI: 1.308 – 8.37). Conclusions: Maternal anaemia during pregnancy, chronic hypertension and low birth weight were significantly associated with perinatal asphyxia. Therefore, early screening and appropriate intervention during pregnancy and intra-partum might reduce perinatal asphyxia among newborns.